Plastid-encoded RNA polymerase variation in Pelargonium sect Ciconium - FC Breman; JW Korver; RC Snijder; C Villard; ME Schranz; FT Bakker (Horticulture Advances, 2024)
Abstract Cyto-Nuclear Incompatibility (CNI), in which there is a mismatch in the interaction between organelles and nucleus, impacts plant species evolution as it has a direct effect on the fitness of plants. It can reduce fertility and/or result in bleached plants devoid of functional chloroplasts. Understanding the processes leading to CNI could help to improve breeding efforts, especially in cases where species with desirable traits need to be crossed into existing cultivars. To better understand the occurrence of CNI and its effects on plant phenotype, we combined near comprehensive crossing series across a clade of species from Pelargonium section Ciconium with comparative genomics and protein modelling for plastid-encoded RNA polymerase (PEP), as the rpo genes encoding PEP subunits were found to be unusually highly divergent, especially in two length-variable regions. Of all plastome-encoded genes, we found these genes to contain more variation than observed across angiosperms and that this underlies structural variation inferred for PEP in P. sect. Ciconium. This variation, resulting in differing physico-chemical properties of the rpo-encoded peptides, provides a possible explanation for the observed CNI, but we cannot directly correlate plastid related CNI phenotypes to rpo genotypes. This suggests that more than one interaction between the nuclear genome and the plastome genes are needed to fully explain the observed patterns.